2019
DOI: 10.1590/1980-265x-tce-2018-0260
|View full text |Cite
|
Sign up to set email alerts
|

Skin-to-Skin Contact Followed by Breastfeeding in the First Hour of Life: Associated Factors and Influences on Exclusive Breastfeeding

Abstract: Objective: to verify the factors associated with the practice of skin-to-skin contact with breastfeeding in the first hour of life and its influence on exclusive breastfeeding in the first month. Method: a retrospective cross-sectional study with medical records from a breastfeeding outpatient clinic in São Paulo, Brazil. The sample included all the medical records of the mother-baby dyad who had been consulted by nurses between 2004 and 2010. Data were collected from the medical records between 2014 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 24 publications
5
15
0
15
Order By: Relevance
“…In this study, we found a high prevalence of complement offer, which corroborates the ndings of studies conducted in other countries and in Brazilian cities [2,14,15,19]. Although the WHO recommends skin-toskin contact at birth, breastfeeding in the rst hour of life and "Do not give the newborn baby any food or drink other than breast milk, unless such procedure has a medical indication", most NB received the complement in the rst hours and days after birth.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, we found a high prevalence of complement offer, which corroborates the ndings of studies conducted in other countries and in Brazilian cities [2,14,15,19]. Although the WHO recommends skin-toskin contact at birth, breastfeeding in the rst hour of life and "Do not give the newborn baby any food or drink other than breast milk, unless such procedure has a medical indication", most NB received the complement in the rst hours and days after birth.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, more than 80% of NB received it in quantity less than or equal to 10 mL, which corresponds to the approximate volume of colostrum produced in each feeding in the rst week of life. The pertinent literature points out complement volumes higher than those of the present research, initially varying from 30 to 57 mL, progressing to about 100 mL on the fourth day and reducing to, on average, 26 mL in the period of discharge [6,19].…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Chama atenção que, embora aproximadamente um quarto das mulheres estar na adolescência, considerado um fator de risco para a não realização do contato pele a pele precoce e de amamentação na primeira hora de vida, essa característica materna não esteve associada ao uso de complemento lácteo, diferentemente de pesquisa realizada em São Paulo, Brasil, na qual a idade materna, especificamente mulheres mais jovens, esteve correlacionada a não realização dessas práticas 13 .…”
Section: Discussionunclassified
“…As políticas públicas devem ser entendidas como um conjunto de medidas, representadas através de programas, planos e metas, criadas pelos governos, voltadas à garantia de acesso pela população aos direitos estabelecidos por Lei, tais como a assistência ou prestação de serviços. Essas medidas integram parte importante da administração pública, já que representam as ações dos governos criadas para melhor atender as necessidades dos cidadãos [11][12][13] . O risco é um fenômeno coletivo, que atinge uma população.…”
Section: Referencial Teóricounclassified